Information technology-based waste management at the Sukoharjo Pati landfill with an importance performance analysis approach - Metadelphi Werdianto; Nany Yuliastuti; Mochamad Arief Budihardjo (Green and Tropical Laboratory for Sustainability, 2025)
Background: Waste management is a crucial issue in achieving a clean and sustainable environment, necessitating the use of environmental information technology to improve its effectiveness. However, the effectiveness of this technology in waste management at final disposal sites still requires further analysis to meet public expectations and satisfaction. Objectives: This study aims to analyze environmental information technology-based waste management at the Sukoharjo Landfill, Pati Regency, using the Importance Performance Analysis (IPA) approach. Methods: The evaluation method is used to measure the effectiveness of waste management with data collected through surveys, interviews, observations, and literature studies. Data analysis was carried out quantitatively using the IPA method and qualitatively using descriptive-interactive techniques based on the stages of Miles and Huberman. Results: The results of the study show: (1) waste management includes all stages of management, namely planning, organizing, implementing, monitoring, evaluating, and following up; (2) environmental information technology is effective and satisfies the community, with 86.27% of respondents rating its performance as very good and 92.85% feeling satisfied; and (3) the IPA approach shows very high management performance (80.03%) and community expectations are met (87.13%). Conclusion: The results of the study show that the use of environmental information technology in waste management at the Sukoharjo Landfill has proven effective and is able to meet expectations and increase community satisfaction.